A Methodology to Estimate the Interest Rate Yield Curve in Illiquid Market: The Tunisian Case. (December 2014) - Chakroun, Fatma; Abid, Fathi
The aim of this article is to develop a methodology to estimate the interest rate yield curve and its dynamics in the Tunisian bond market, which is considered as an illiquid market with a low trading volume. To achieve this, first, we apply the cubic spline interpolation method to deal with the missing observation problem. Second, we focus on the work of Vasicek (1977 ) and Cox-Ingersoll and Ross (CIR) (1985), we estimate each model and discuss its performance in predicting the dynamics of the interest rate yield curve using ordinary least squares (OLS) and maximum likelihood estimation (MLE) methods. The data sample consists of Treasury bond prices for the period from 14 July 2004 to 10 September 2012 collected from over the counter market. This assessment is done by Matlab software using the specified algorithms. The results suggest that the cubic spline method is accurate for construction of the average interest rate yield curve. Then, the estimation of Vasicek (1977 ) and CIR (1985) models generate an upward sloping yield curves and the Vasicek (1977 ) model shows more ability to replicate the stylised facts of the short-term interest rates in the Tunisian bond market. Finally, the forecasting of the yield curve predicts an economic growth in the future characterised by a higher inflation. JEL Classification: G12